Cloning, expression and sequence analysis of Al gene in Aeromonas hydrophila strains TPS-30 and BSK-10 - PAN Xiao-yi; SHEN Jin-yu; HAO Gui-jie; YAO Jia-yun; XU Yang (浙江大学学报. 农业与生命科学版)
Adhesin is an important pathogenic factor of Aeromonas hydrophila which can cause disease in most fish in the area of Jiangsu and Zhejiang. The strains of TPS-30 and BSK-10 were assigned to serogroup O:9 and O:97 respectively, and the genes of the major adhesin (designated as Al) of the two strains were cloned and sequenced. The results revealed that there was a mutation region in the N-terminal domain in the Al sequences of the two strains, and the mutation area of TPS-30 was a bit shorter than that of BSK-10. The Al of TPS-30 was cloned in the vector pET28a(+) and expressed in Escherichia coli BL21(DE3). A band of 41 ku fusion protein of A l was confirmed by the sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The expressed protein products reached a peak after 6 h of induction and accounted for 44.0% of whole bacterial protein. Carassius Auratus Gibelio vaccinated with the fusion adhesin produced a significant immune response against A. hydrophila. The antibody titer reached the highest at the 5th week of vaccination. The relative percentage survivals (RPS) of TPS-30 and BSK-10 were 94.7% and 77.8%, respectively. Therefore, the recombinant strain BL21 (DE3) (pET28a-AHal) could be used to develop recombinant subunit vaccines against the infection of A. hydrophila.